Traditional Chinese Medicine in Patients With Primary Sjogren's Syndrome: A Randomized, Double-Blind, Placebo-Controlled Clinical Trial - Chen, Huang-Hsi; Lai, Jung-Nien; Yu, Min-Chien; Chen, Chia-Yin; Hsieh, Yi-Ting; Hsu, Yi-Fan; Wei, James Cheng-Chung (Frontiers in Medicine, 2021)
Sjogren’s syndrome (SS) is a chronic inflammatory autoimmune disease characterized by dryness, fatigue, and pain. Current therapies for SS in Western medicine are limited. To explore the efficacy and safety of using a traditional Chinese medicine (TCM) formula on patients with primary SS, we performed a 12-week, randomized, double-blinded, placebo-controlled clinical trial at Chung Shan Medical University Hospital. We included 42 patients with SS between the ages of 20 and 80 years who met the classification criteria of the American and European Consensus Group (AECG). Patients who had other severe systemic manifestations or diseases were excluded. After screening 42 patients were randomly assigned to the TCM treatment group or placebo group (ratio of 2:1). We treated the TCM group with 6 g of Gan-Lu-Yin granules after breakfast and 6 g of Jia-Wei-Xiao-Yao-San combined with 1 g of Suan-Zao-Ren-Tang and 1 g of Ye-Jiao-Teng after dinner. Patients in the control group were treated with placebo in one-tenth dosage of the treatment group. The European League Against Rheumatism Sjogren’s Syndrome Patient-Reported Index (ESSPRI) was used as the primary endpoint at week 12. Secondary endpoints were the Sjogren’s Syndrome Disease Activity Index (SSDAI), physician global assessment (PGA), visual analogue scale (VAS), Multidimensional Fatigue Inventory, Medical Outcomes Survey Short Form-36, and the Pittsburgh Sleep Quality Score (PSQI). Adverse events were also recorded. 28 patients were assigned to the TCM treatment group and 14 patients were assigned to the controlled group. During the period, 5 patients withdrew from the TCM group and 7 from the control group. At week 12, the ESSPRI score of the treatment group decreased by 0.62 (95% CI P = 0.557) and that of the placebo group decreased by 0.91 (P = 0.557). However, no significant difference was observed between the 2 groups. Compared with the placebo group (−0.21), sleep duration in the PSQI was improved with the TCM group (−0.61, P = 0.914). At week 12, the ESSPRI scores didn't reveal that TCM formula was efficacious for treating SS. However, the PSQI scores indicated that this formula could prolong patient sleep duration which could also decrease the blood pressure.